2008
DOI: 10.1016/j.cub.2008.04.050
|View full text |Cite
|
Sign up to set email alerts
|

CED-10/Rac1 Mediates Axon Guidance by Regulating the Asymmetric Distribution of MIG-10/Lamellipodin

Abstract: Axon migrations are guided by extracellular cues that induce asymmetric outgrowth activity in the growth cone. Several intracellular signaling proteins have been implicated in the guidance response. However, how these proteins interact to generate asymmetric outgrowth activity is unknown. Here, we present evidence that in C. elegans, the CED-10/Rac1 GTPase binds to and causes asymmetric localization of MIG-10/lamellipodin, a protein that regulates actin polymerization and has outgrowth-promoting activity in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
81
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 30 publications
4
81
0
Order By: Relevance
“…We have proposed that a signaling module comprising UNC-6, UNC-40, PI3K, Rac, and MIG-10 (lamellipodin) becomes asymmetrically localized in the C. elegans AVM and HSN neurons Chang et al 2006;Quinn et al 2006Quinn et al , 2008. This localization is proposed to polarize the response and to amplify the shallow external UNC-6 gradient.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have proposed that a signaling module comprising UNC-6, UNC-40, PI3K, Rac, and MIG-10 (lamellipodin) becomes asymmetrically localized in the C. elegans AVM and HSN neurons Chang et al 2006;Quinn et al 2006Quinn et al , 2008. This localization is proposed to polarize the response and to amplify the shallow external UNC-6 gradient.…”
Section: Resultsmentioning
confidence: 99%
“…In AVM and HSN, a signaling module comprising UNC-6, UNC-40, phosphoinositide 3-kinase (PI3K), Rac, and MIG-10 (lamellipodin) is thought to transmit the directional information provided by the graded distribution of extracellular guidance cues to the internal cellular machinery that promotes directed outgrowth Chang et al 2006;Quinn et al 2006Quinn et al , 2008. MIG-10 appears to provide an important link because this family of proteins can interact with proteins that promote actin polymerization, and it is associated with asymmetric concentrations of f-actin and microtubules in turning growth cones (Krause et al 2004;Quinn et al 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Further study will be required whether the Lpd-mediated actin-based cytoskeletal regulation system is also involved in Sema4D-mediated axonal growth cone collapse. A recent report has shown that Mig-10, a C. elegans Lpd ortholog, interacts with active Rac, a Rho family protein, and Mig-10 regulates axon guidance downstream of Rac in response to netrin and slit (Quinn et al, 2008). The Plexin-B subfamily has been shown to bind to Rac and inhibit its signaling (Hu et al, 2001;Vikis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%